Issues, challenges and future of female employees at the hotel industry in sabah: a post covid-19 investigation - Wirawati Ngui Yi Xe; Arif Kamisan Pusiran; Andi Tamsang Andi Kele; Sharija Shaari; Jennifer Chan Kim Lian (Penerbit Universiti Malaysia Sabah, 2024)
The hotel industry is one of the industries that was severely impacted by the COVID-19 pandemic due to the global shut down of travel and tourism throughout the pandemic. This inevitably affected the hotel industry and the numerous employees in the female-dominated industry. The impact of COVID-19 on the hotel industry and female employment in the industry is likewise observed in Sabah, a touristic state in Malaysia. This study aimed to investigate the issues and challenges faced by female employes to remain in the hotel industry in Sabah during the pandemic. In addition, the study also revealed the future prospects for women in the hotel industry following the pandemic. In order to uncover the insights of female employees in the hotel industry, a qualitative research design was employed. Purposive sampling was used to recruit respondents who worked in the hotel industry when the COVID-19 pandemic hit the nation and when the hotel industry started to re-open in Malaysia. A total of 12 female employees in the hotel industry in Sabah were interviewed to investigate their experiences as hotel employees. The data were then transcribed and analyzed using thematic analysis. The findings revealed the issues and challenges faces by female employees included the bleak outlook for the industry, having to achieve work targets, and managing team members. The findings of this study contributed to gender studies of the hotel especially in the midst of crisis and provide ideas for elevating women in the hostel industry.